Pengaruh Model Pembelajaran Perubahan Konseptual Terhadap Kemampuan Berpikir Kreatif Fisika Peserta Didik Kelas XI - Sri Rahma Wati; Muhammad Taufik; Ahmad Harjono; Muhammad Zuhdi (Jurnal Penelitian dan Pembelajaran Fisika Indonesia, 2020)
This research aims to examine the effect of conceptual change learning model on the creative thingking abilities of physics class XI students at MAN 1 Lombok Barat . This type of research is quasi experiment with pretest-posttest control group design. The research popuplation was all students of XI MIA MAN 1 Lombok Barat. Sampling technique of this research use saturated sampling so that there are two classes that is XI MIA 2 as the experimental class and XI MIA 1 as the control class. The experimental class was treated in the form of a conceptual change learning and the control class was treated in the form of a conventional learning model. Hypothesis testing of this research is Polled Variance t-test. The conclution of this research is there is the effect of conceptual change learning model on the creative thingking abilities of physics class XI students